A new and more precise experiment method for characterizing the mineralogical heterogeneity of unconventional hydrocarbon reservoirs. (15th November 2018) - Du, Shuheng; Pang, Shan; Shi, Yongmin
Abstract: This study is aimed to introduce the new and more precise experiment method which could characterize the mineralogical heterogeneity of unconventional hydrocarbon reservoirs. As the 2D characterization methods and techniques still have a large amount of information to be excavated with quite strong vitality, the new method could be used to discover the minerals directly under the FE-SEM combining with the EDS method after considering both the resolution (10 nm) and representativeness (20 mm). The higher the ratio of the maximum to the minimum and the mean square deviation of each mineral parameter in thin sections from 8 different directions, the higher the microscopic heterogeneity of the reservoir. The new method would help to the study on enhancing the remaining unconventional hydrocarbon recovery.